Effectiveness of non-pharmacological falls prevention interventions for people with Multiple Sclerosis, Parkinson’s Disease and stroke: protocol for an umbrella review - O'Malley, Nicola (HRB Open Res, 2020)
Background: Falls are common among people with neurological diseases and have many negative physical, psychosocial and economic consequences. Implementation of single-diagnosis falls prevention interventions is currently problematic due to lack of participants and resources. Given the similarities in falls risk factors across stroke, Parkinson’s Disease (PD) and Multiple Sclerosis (MS), the development of an intervention designed for mixed neurological populations seems plausible and may provide a pragmatic solution to current implementation challenges. This umbrella review aims to summarise the totality of evidence regarding the effectiveness of non-pharmacological falls prevention interventions for people with MS, PD and stroke and identify the commonalities and differences between effective interventions for each disease to inform the development of an evidence-based intervention that can be tailored for people with mixed diagnoses. Methods: This umbrella review will be conducted and reported in accordance with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) statement. 15 electronic databases and grey literature will be searched. Systematic reviews of randomised controlled trials and studies investigating the effects of non-pharmacological falls prevention interventions on falls outcomes among people with MS, PD and stroke will be included. Methodological quality of included reviews will be assessed using the Assessment of Multiple Systematic Reviews 2 tool. The Grading of Recommendations Assessments, Development and Evaluation framework will be used to rate the quality of evidence. A summary of evidence table and narrative synthesis will be utilised to clearly indicate the findings. Discussion: This umbrella review presents a novel and timely approach to synthesise existing falls literature to identify effective non-pharmacological interventions for people with MS, PD and stroke. Of importance, a robust methodology will be used to explore the differences and similarities in effective interventions for individuals with these neurological conditions to facilitate the development of an intervention for these mixed neurological groups.